FROM PUBLIC-SCHOOL TEACHING TO DIVISION-OFFICE EDUCATIONAL ADMINISTRATION: A LONGITUDINAL AUTOETHNOGRAPHY - Cyrus Pontawe Casingal (EDUCATIONE, 2027)
Moving from classroom teaching to system-level educational administration requires both technical role learning and reconstruction of professional identity. This longitudinal analytic autoethnography examined my transition from nine years of public-school teaching to a division-office education specialist role during the first 16 months of appointment, from August 2024 to November 2025. The study asked how I experienced and interpreted changes in role expectations, professional identity, and engagement with system-level educational constraints. Data were generated through contemporaneous experiential journals, bi-weekly artifact-based reflections, and monthly retrospective entries linking the new role with prior teaching experience. A six-phase reflexive thematic analysis was conducted, followed by interpretation through role identity theory and complexity leadership theory. Three interrelated themes were developed: navigating ambiguous and expanding role expectations, negotiating continuity between pedagogical and administrative identities, and translating classroom experience into context-sensitive responses to system-level constraints. The analysis shows that the transition involved neither abandonment of the teacher identity nor a simple acquisition of administrative procedures. Instead, pedagogical commitments became resources for interpreting policy, coordination, and organizational responsibility. The study contributes a role-specific account of division-office administration and proposes that induction and mentoring should address identity negotiation alongside technical competence. The findings are analytically transferable but remain bounded to one participant and one organizational setting.